Pelaksanaan Kegiatan Sosialisasi Anti Bullying melalui Mini Bisokop pada Siswa Sekolah Dasar di SD Negeri Simaja - Ayu Ghinadi; Binar Agni Jembarwati; Parida Dwi Astuti; Siti Fatimah; Widia Nur Jannah; Muhammad Lutfi (Mathematics Education Study Program, 2025)
Bullying is a serious problem in Indonesia's educational environment that requires a comprehensive approach. This study aims to analyze the bullying prevention socialization program through mini cinema at SD Negeri Simaja using descriptive qualitative method. Activities were carried out for students in grades 4, 5, and 6, using an interactive approach with three main activities, namely, screening educational films, active discussions, and giving rewards. The results showed that the program succeeded in raising students' awareness about various forms of bullying, including verbal, physical and social bullying. Through the movie themed “say no to bullying, say yes to friedship”, students were able to identify bullying and its psychological impact. Interactive discussions and reward systems proved effective in encouraging students' active participation. The main obstacles include students' limited understanding of bullying and the psychological constraints of shy students. Strategies to overcome these obstacles were through providing in-depth context before the movie screening, and a gradual approach to invite students to be more active.